Understanding the Effectiveness of Blended Learning as a Learning Tool in Tertiary Education in Malaysia - Arulanandam, Benedict Valentine*; Ragunathan, Chitra Devi*; Selvaraja, Prema*; Sajnani, Sunil Kishor* (Human Resource Management Academic Research Society (www.hrmars.com), 2019)
Technology has grown by leaps and bounds, penetrating every stratum of society, industry and government. As much as technology has assisted mankind in her endeavours to progress, it is no doubt that technology has brought ‘new wine into an old wineskin”, bearing fruits of efficiency in every sector of life. Hinssen (2010) expresses well in that, technologies will no longer be termed as technology, but it will find its embrace in daily living with zero tolerance for failure. It is clear that technology is influencing education industry in an unprecedented way. With blended learning, technology tools acting as catalyst are inspiring learning and correctly addressing the expectation of people, especially the younger generation. This study examines the effectiveness of blended learning among five academic programs within Sunway College. This study was motivated by the lack of data on the effectiveness of blended learning at the College level, having implemented it over the last 3 years from the time of this study. An in-depth questionnaire was distributed to a sample size of 745 students (learners) across the 5 programs with the aim to discover the viability of our blended learning, which was implemented over the last three years in the College. Both quantitative and qualitative methods were applied in this study. Blended learning is a learning approach which draws insights from theories linking to behavior and constructivism. This study adopts the social constructivist theory, in which learning experiences and interactions are taken into consideration. The findings reveal a rich source of information on blended learning in each program and the necessary opportunities for improvements in tandem with the cognitive responses of the current generation in our classrooms.